Quality of life and associated factors among HIV positive patients after completion of treatment for Cryptococcal meningitis - Kitonsa, J; Kiwanuka, J; Anywaine, Z; Kansiime, S; Katumba, K; Aeron, N; Beardsley, J; Kibengo, F; Gray, A; Kaleebu, P; Day, J (Public Library of Science, 2021)
Background Cryptococcal meningitis (CCM) remains one of the leading causes of mortality among HIV infected patients. Due to factors such as the severity of CCM pathology, the quality of life (QOL) of patients post-treatment is likely to be poor. Few studies have reported on QOL of CCM patients post treatment completion. We used data collected among patients in the CryptoDex trial (ISRCTN59144167) to determine QOL and associated factors at week 10 and six months from treatment initiation. Methodology CryptoDex was a double-blind placebo-controlled trial of adjunctive dexamethasone in HIV infected adults with CCM, conducted between 2013 and 2015 in six countries in Asia and Africa. QOL was determined using the descriptive and Visual Analog Scales (VAS) of the EuroQol Five-Dimension-Three-Level (EQ-5D-3L) tool. We derived index scores, and described these and the VAS scores at 10 weeks and 6 months; and used linear regression to determine the relationship between various characteristics and VAS scores at both time points. VAS scores were interpreted as very good (81–100), good (51–80), normal (31–50) and bad/very bad (0–30). Results Of 451 patients enrolled in the trial, 238 had QOL evaluations at week 10. At baseline, their mean age (SD) was 35.2(8.5) years. The mean index scores (SD) were 0.785(0.2) and 0.619(0.4) among African and Asian patients respectively at week 10, and 0.879(0.2) and 0.731(0.4) among African and Asian patients respectively at month six. The overall mean VAS score (SD) at 10 weeks was 57.2 (29.7), increasing significantly to 72(27.4) at month six (p<0.001). At week 10, higher VAS score was associated with greater weight (p = 0.007) and being African (p<0.001), while lower VAS score was associated with positive yeast culture at day 14 (p = 0.026). At month six, higher VAS score remained associated with African origin (p = 0.006) while lower VAS score was associated with positive yeast culture (p = 0.006). Lower VAS scores were associated with higher number of inpatient days at 10 weeks and 6 months (p = 0.003 and 0.002 respectively). Conclusion QOL was good among patients that had completed therapy for CCM, but below perfect. Strategies to improve QOL among CCM survivors are required.